Children's rights and food marketing : state duties in obesity prevention - Ó Cathaoir, Katharina (Cambridge : Intersentia, 2022)
This book provides a thorough account of states' obligations to prevent childhood obesity under the Convention on the Rights of the Child, focusing on restricting unhealthy food marketing to children. It argues that while political momentum is sluggish and stilted, children's rights provide a compelling basis for action. This is important because unhealthy food marketing is a transnational concern that no one state can effectively regulate alone. Furthermore, the book fills gaps in research on socioeconomic rights by offering an analysis of states' obligations under the rights to health and nutrition in relation to non-communicable disease prevention in high-income states. The book avoids a myopic focus, examining state obligations in the context of conflicting and complementary international duties including international health law, the European Convention on Human Rights, European Union law and international trade law. Children's Rights and Food Marketing focuses on the CRC as it binds all states parties to a basic framework, which, if fully implemented, provides children in developed and developing countries with entitlements to universal standards. Besides analysing state obligations, the book presents a blueprint for what a child rights approach to regulating unhealthy food marketing could look like. It focuses on the restriction of unhealthy food marketing in the European Union, spanning consumer protection, media law and data protection law. This book is of interest to academics, practitioners and organisations working in the field of public health law and children's rights.
Title from publisher's bibliographic system (viewed on 16 Dec 2022).
Keywords: Convention on the Rights of the Child -- (1989 November 20); Convention for the Protection of Human Rights and Fundamental Freedoms -- (1950 November 5); Food law and legislation -- Europe; Obesity in children -- Europe; Children's rights -- Europe; Food industry and trade -- Marketing; Obesity in children -- Prevention -- Law and legislation -- Europe